KAJIAN PENGGUNAAN MODA TRANSPORTASI SUNGAI DI KOTA JAMBI - , YOSEPHINE HARMIS KARTINI, Dr. M.R. Djarot Sadharto W., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of transportation, day by day have been increasing as far as technology development. The existence of two bridgesand one of bridge project which have being built for pedestrians in Jambi city should be wished offthe using and the presence of river transportation. But until now, the rivertransportationis still used in spite of the user of it is on the wane.This case is certainly influenced by many factors, so it is important to knowing the affecttingfactors ofuseness of this river transportation. This studyaims 1) to describe the using development of river transportation,2) to identify the affectingfactors ofuseness of river transportation, 3) todescribe the public's perception of the rivertransportion andits existence, also 4) to offerthe proper policy inputfor the existence and the sustainability of river transportation in Jambi city. This study was survey research. Theboundaryes area of this study wasKecamatan Pasar Jambi, Pelayangan and Danau Teluk as the center of river traffic lane. The analytical method that used was descriptive qualitative and quantitative that refer to the information from key person and used regression analysis by model criteria selection. The result that was collectedis 1) the river transportation, in the past, used a rowboat and human powers as the force driving source.Then, in the 1976 until now,it have been using power motor engine wich facilitating the traffic-lane.2) The affecting factors ofuseness of rivertransportationare the travel destination, the traveling schedule, the price of ticket, the time effectiveness and the ride comfortness. 3) The public perception of the river transportation services has been quite good. The society also considers that the river transportis still very important and necessary.4) The government have to pay attention of the river transportaionâs existence and management. The existence of this kind transportation is not only as a transportation facility, but also could be develop into tourism transportation that cold attract tourists or investors to support the concept of regional waterfront city development so that the welfare of people could be increasing.